2011
DOI: 10.1105/tpc.110.081281
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Resolution of Polyploidy in theArabidopsisMetabolic Network Gives Rise to Relative and Absolute Dosage Constraints

Abstract: The abundance of detected ancient polyploids in extant genomes raises questions regarding evolution after whole-genome duplication (WGD). For instance, what rules govern the preservation or loss of the duplicated genes created by WGD? We explore this question by contrasting two possible preservation forces: selection on relative and absolute gene dosages. Constraints on the relative dosages of central network genes represent an important force for maintaining duplicates (the dosage balance hypothesis). However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
142
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 85 publications
13
142
0
Order By: Relevance
“…For example, more single subgenome genes were detected in D subgenome compared with A and B subgenomes in chromosomes 4, 6 and 7 (Table 1). Both the results presented here and those from previous studies showed differential gene loss between A, B and D subgenomes, further supporting the proposed theories for selective gene retention and loss after polyploidization (Bekaert et al 2011;De Smet et al 2013). …”
Section: Discussionsupporting
confidence: 79%
“…For example, more single subgenome genes were detected in D subgenome compared with A and B subgenomes in chromosomes 4, 6 and 7 (Table 1). Both the results presented here and those from previous studies showed differential gene loss between A, B and D subgenomes, further supporting the proposed theories for selective gene retention and loss after polyploidization (Bekaert et al 2011;De Smet et al 2013). …”
Section: Discussionsupporting
confidence: 79%
“…Although the prevalence of WGD within the angiosperms is well established and the discussion has now shifted toward which degree of importance can be attributed to WGDs in the light of evolutionary success Bekaert et al, 2011;Mayrose et al, 2011Mayrose et al, , 2015Arrigo and Barker, 2012;Soltis et al, 2014), both the prevalence and evolutionary consequences of WGDs remain largely unexplored in nonangiosperm plant clades (Soltis and Soltis, 2013). Here, we demonstrated that a paleopolyploidy event has also occurred within the horsetails.…”
Section: The Paleopolyploidy May Have Contributed To the Long-term Sumentioning
confidence: 89%
“…In total, 15 GO-slim labels showed enrichment. These included many genes in categories such as regulation of biological process, growth, and ribosome and signal transduction, typical for regulatory and developmental genes that are often highly connected and present in macromolecular complexes and/or stoichiometric pathways, which have frequently been observed before to be overrepresented and retained long after the WGD event itself in several angiosperm and metazoan genomes (Hakes et al, 2007;Freeling, 2009;Bekaert et al, 2011;Rodgers-Melnick et al, 2012). This is confirmed by the more extensive list of full GO terms that are found to be overrepresented in the homoeologs, where again many genes with roles that can be associated with plant regulation and development are found (Supplemental Data Set 1).…”
Section: Regulatory and Developmental Genes Are Overrepresented In Thmentioning
confidence: 99%
“…Models of budding yeast gene networks suggest that WGD likely contributed to increased flux in the glycolytic pathways, which confers a fitness benefit in high-Glc environments (van Hoek and Hogeweg, 2009). Similarly, in Arabidopsis, duplicate retention after WGD is associated with reactions with high metabolic flux (Bekaert et al, 2011), suggesting that increased gene dosage results in increased metabolic activity, which may be beneficial. The impact of duplicate gene dosage is emphasized in a recent review (Conant et al, 2014).…”
Section: Selection On Existing Functionsmentioning
confidence: 99%